System Thinking Scales and Learning Environment of Family Planning Field Workers in East Java - Dwi Listyawardani; Iswari Hariastuti (International Journal of Evaluation and Research in Education (IJERE), 2016)
Systems thinking is needed due to the growing complexity of the problems faced family planning field workers in the external environment that is constantly changing. System thinking ability could not be separated from efforts to develop learning for the workers, both learning at the individual, group, or organization level. The design of the study was quantitative study using cross-sectional study. There is a relationship between the scale of field worker’s system thinking with the learning environment at organization level (p 0.017<α). The characteristic factors; individual, team/group learning environment; are unrelated to the system thinking scales. There are also relationship among learning environments. Individuals learning on systems thinking for field workers are highly needed as a basic capital in the development of human resources. The training/learning done so far needs to be revitalized, that is reconstructing the learning materials or modules taught so as learning can be run more effectively and leads to increase the ability of systems thinking. Organizationrelated to the implementation of field worker tasks lies in the central, provincial and districts/municipalities level, need to facilitate the learning; both at the individual, group/team, and organizational level itself. Learning and guidance need to be developed into a useful integrated mechanism, not only for individuals but also for the organization.